Prevalence, Perceptions and Correlates of Physical Activity Among Youth in New Zealand - Hohepa, Maea (Auckland University of Technology, 2008)
Sufficient physical activity, a key prerequisite for health, is lacking in many teenagers. Limited knowledge, however, exists about who, when, why, and if New Zealand teenagers are getting their daily dose of health-related physical activity. At conception of this thesis, available information was predominantly survey-derived with no New Zealand data and few international studies that had assessed adolescent physical activity levels objectively. Data were collected from three projects. Convenience sampling was used across all projects to recruit students from low-decile high schools located in the Auckland region. For Project 1, 236 Year 9 to Year 13 students each wore a pedometer for five days (three weekdays and two weekend days) and reported their mode of transportation to and from school. To explore ethnic and sex-specific perceptions of physical activity among youth (i.e., barriers, benefits, potential physical activity enhancing strategies), Project 2 involved nine focus group discussions with 44 Year 9 and Year 10 students who identified as Māori or European. Project 3 was a large cross-sectional study of 3,451 high school students (Years 9 - 13) from seven low-decile schools. Through this project the following self-reported data were collected: demographics, physical activity levels during four school-day physical activity opportunities (i.e., active travel, lunchtime physical activity, recess physical activity, after-school physical activity), sedentary behaviour (i.e., school-day television (TV) watching), level of perceived encouragement to be active, and the presence of home policies regarding TV use. Analyses revealed low physical activity participation and high TV use behaviours. Pedometer data showed that only 14.5% of participants achieved a conservative criterion of 10,000 steps daily. Also, daily steps varied by age group (junior students: 11,079 ± 330; senior students: 9,422 ± 334), sex (males: 10,849 ± 381; females: 9,652 ± 289), time of week (weekday: 12,259 ± 287; weekend day: 8,241 ± 329), and transportation mode to/from school (walkers: 13,308 ± 483; car transit users: 10,986 ± 435). Low school-day physical activity levels emerged, especially during school hours (i.e., during recess and lunchtime). Based on dichotomised grouping (less active versus more active), the proportion of students in the ‘more active’ group during morning recess and lunchtime, after school, and as part of active travel to/from school were 26%, 32.4%, 56.3%, 58.1% respectively. Only 11.1% of participants were in the ‘more active’ group across all four physical activity opportunities. The focus group data revealed primarily social benefits of physical activity (e.g., meeting new people, fun). Barriers were mainly environment-related and included lack of peer support, low accessibility to and availability of physical activity opportunities, alternative sedentary activities, structure of physical education classes (females only), and distance between home and school (in terms of active transportation). Potential strategies to increase physical activity reflected the articulated barriers and benefits (e.g., increase peer support, parents to turn off the TV, organised activities at school, restructure physical education classes to allow student involvement in the decision-making process of class content). No ethnic and few sex differences in perceptions were found. Focusing on the verbalised importance of social support from the focus groups, Project 3 data showed that the strength of association between perceived encouragement from different support sources (i.e., parents, older siblings/cousins, peers, school) and physical activity participation varied by the physical activity opportunity examined. In particular, multivariate logistical regression showed reduced odds of being in the ‘more active’ group was associated with low parental encouragement (Juniors, OR: 0.47, 95% CI: 0.38-0.58; Seniors, OR: 0.41, 95% CI: 0.29-0.60) and low peer encouragement (Juniors, OR: 0.61, 95% CI: 0.51-0.74; Seniors, OR: 0.49, 95% CI: 0.35-0.69) for after-school physical activity, low peer encouragement (Juniors, OR: 0.39, 95% CI: 0.32-0.48; Seniors, OR: 0.41, 95% CI: 0.29-0.57) for lunchtime activity, and low peer encouragement (Juniors, OR: 0.78, 95% CI: 0.66-0.92) for active transportation (junior students only). No significant difference in physical activity was found between students who received high encouragement from two parents than students who reported high encouragement from their sole parent in a single parent family. Concentrating on the after-school period, Project 3 data were analysed to examined the relevance of the displacement hypothesis during this school-day period. The association between parental strategies (i.e., encouragement to be active and having TV limits) and youth after-school activity behaviours (i.e., hours spent viewing TV, physical activity participation) was also examined. Support for the displacement hypothesis emerged. In particular, compared to students who watched less than one hour of TV, those who watched greater than four hours of TV were half as likely to be in the more active group for after-school physical activity participation (adjusted OR: 0.51; 95% CI: 0.40-0.65). Comparing activity profile groups (i.e., based on combined TV use and after-school activity levels), compared to the participants in the ‘low TV/active’ group, participants in the other three activity groups (e.g., ‘high TV/low active’) were at least 1.28 times more likely to have parents that executed only one parental strategy and up to 4.77 times more likely to have parents that did not carry out either strategy. Substantive opportunities exist for youth to be active every day, and in different contexts and environments, yet a large proportion of young people are not maximising these opportunities to be active. If the health issue of inactivity is to be tackled in a comprehensive and efficient manner, a multi-strategy, multi-environment, coordinated approach among local authorities, government agencies, schools, families, and neighbourhoods is required to address the noted policy, physical, and social-related associates of an active lifestyle for youth. Future effort, whether in the form of strategy development, intervention work, or research, needs to be founded upon ecological theory, where both individual and a range of familial, social, and physical environmental factors (and there potential interactions) are considered. Lastly, equal research attention should be directed at improved physical activity levels, and just as importantly, reducing time youth spend in a sedentary state.
Keywords: Physical activity; Adolescence; Television watching; Questionnaire; Focus groups; Youth-centred approach